2015
DOI: 10.1038/nn.3960
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial control by DRP1 in brain tumor initiating cells

Abstract: Brain tumor initiating cells (BTICs) coopt the neuronal high affinity GLUT3 glucose transporter to withstand metabolic stress. Here, we investigated another mechanism critical to brain metabolism, mitochondrial morphology. BTICs displayed mitochondrial fragmentation relative to non-BTICs, suggesting that BTICs have increased mitochondrial fission. The essential mediator of mitochondrial fission, dynamin-related protein 1 (DRP1), was activated in BTICs and inhibited in non-BTICs. Targeting DRP1 using RNA interf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
334
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 337 publications
(357 citation statements)
references
References 51 publications
20
334
2
1
Order By: Relevance
“…Where indicated, BTICs and non-BTICs were derived immediately after dissociation or after transient xenograft passage in immunocompromised mice using prospective sorting followed by assays to confirm stem cell marker expression, sphere formation, and secondary tumor initiation. Although CD133 is controversial, in the models used in these studies, CD133 has previously identified functional BTICs (2,30). Therefore, in experiments with matched TIC and non-TIC cultures, we segregated AC133 marker-positive and marker-negative populations using an APC-conjugated anti-CD133/2 antibody (293C3, Miltenyi Biotech) by FACS or magnetic bead separation (Miltenyi Biotech), as previously described (2,30).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Where indicated, BTICs and non-BTICs were derived immediately after dissociation or after transient xenograft passage in immunocompromised mice using prospective sorting followed by assays to confirm stem cell marker expression, sphere formation, and secondary tumor initiation. Although CD133 is controversial, in the models used in these studies, CD133 has previously identified functional BTICs (2,30). Therefore, in experiments with matched TIC and non-TIC cultures, we segregated AC133 marker-positive and marker-negative populations using an APC-conjugated anti-CD133/2 antibody (293C3, Miltenyi Biotech) by FACS or magnetic bead separation (Miltenyi Biotech), as previously described (2,30).…”
Section: Methodsmentioning
confidence: 99%
“…Although CD133 is controversial, in the models used in these studies, CD133 has previously identified functional BTICs (2,30). Therefore, in experiments with matched TIC and non-TIC cultures, we segregated AC133 marker-positive and marker-negative populations using an APC-conjugated anti-CD133/2 antibody (293C3, Miltenyi Biotech) by FACS or magnetic bead separation (Miltenyi Biotech), as previously described (2,30). The TIC phenotype of these cells was validated by stem cell marker expression (CD133, OLIG2, and SOX2), functional assays of self-renewal (serial tumorsphere passage), and tumor propagation by in vivo limiting dilution.…”
Section: Methodsmentioning
confidence: 99%
“…Moving forward, these studies demonstrate the importance of understanding the molecular alterations that are present in recurrent tumors and how these influence the structure of cells within the tumor hierarchy. In addition, it is necessary to consider that therapeutic resistance mechanisms may not be solely innate but may evolve from exposure to microenvironmental factors such as hypoxia and acidic and metabolic stress Li et al 2009b;Hjelmeland et al 2011;Flavahan et al 2013;Xie et al 2015).…”
Section: Therapeutic Resistancementioning
confidence: 99%
“…Furthermore, while total DRP1 levels were similar in normal and neoplastic brain tissues, activating phosphorylation of DRP1 (DRP1 S616 ) was increased in glioblastomas, and a strong inverse correlation was found between DRP1 S616 and poor survival in glioblastoma patients. 69 In this work, the authors suggest that cyclin-dependent kinase 5 (CDK5) was responsible for DRP1 activation in brain TICs and that calcium-/calmodulin-dependent protein kinase type 2 (CAMK2) was responsible for inhibitory phosphorylation of DRP1 in Ser 637 in non-TICs. 69 Since glioblastomas rank among the most lethal cancers, it will be interesting to explore DRP1 inhibition as a therapeutic strategy for these tumors.…”
Section: Mitochondrial Dynamics and Cancermentioning
confidence: 99%